Developing Open-Source Roguelike Games for Visually-Impaired Players by Using Low-Complexity NLP Techniques - Luís Fernández-Núñez; Darío Penas; Jorge Viteri; Carlos Gómez-Rodríguez; Jesús Vilares (Proceedings, 2020)
The prominent graphic component of video games greatly limits the accessibility of this type of entertainment by visually impaired users. We make here an overview of the first games developed within an initiative for the development of roguelike games adapted to visually impaired players by using Natural Language Processing techniques. Our approach consists of integrating a multilingual module that automatically generates text descriptions of what is happening within the game. The user can then read such descriptions by means of a screen reader.